Inadequate Mental Health Literacy and Insufficient Physical Activity Potentially Increase the Risks of Anxiety and Depressive Symptoms in Chinese College Students - Huang, Xuexue; Wang, Xiaoqing; Hu, Jie; Xue, Yanni; Wei, Yanyan; Wan, Yuhui; Song, Xianbing; Wang, Rui; Zhang, Bao; Fang, Jun; Zhang, Shichen (Frontiers in Psychiatry, 2021)
Objective: The present study aimed to examine the interactive associations between physical activity and mental health literacy with anxiety and depressive symptoms in Chinese college students. Methods: A cross-sectional study was conducted from May to July 2020. A total of 7,512 students were recruited from two medical colleges in Hefei and Anqing city in Anhui Province, China. Physical activity, mental health literacy, anxiety and depressive symptoms were measured by self-reported validated instruments. Analyses were conducted with logistic regression models. Results: The prevalence of anxiety and depressive symptoms was 8.3% and 16.3%, respectively. Insufficient physical activity was significantly associated with depressive symptoms (OR=1.284, 95%Cl: 1.115-1.478) and anxiety symptoms (OR=1.366, 95%Cl: 1.128-1.655). Inadequate mental health literacy was significantly associated with depressive symptoms (OR=2.833, 95%Cl: 2.411-3.329) and anxiety symptoms (OR=3.291, 95%Cl: 2.596-4.171). The students who had inadequate mental health literacy and insufficient physical activity had the highest risks of depressive symptoms (OR = 4.170, 95% CI: 3.076-5.652) and anxiety symptoms (OR = 4.427, 95% CI: 2.860-6.852). Conclusion: These finding indicated that Chinese college students having insufficient physical activity and inadequate mental health literacy are at risk of exhibiting anxiety and depressive symptoms. Early intervention programs for college students with mental health problems should be considered to enhance their mental health literacy and to increase their physical activities.